Caring for the elderly: a person-centered segmentation approach for exploring the association between health care needs, mental health care use, and costs in Germany - Wild, Beate; Schellberg, Dieter; Böhlen, Friederike; Schöttker, Ben; Laetsch, Dana Clarissa (PLOS ONE, 2019)
Background: Person-centered care demands the evaluation of needs and preferences of the patients. In this study, we conducted a segmentation analysis of a large sample of older people based on their bio-psycho-social-needs and functioning. The aim of this study was to clarify differences in health care use and costs of the elderly in Germany. Methods: Data was derived from the 8-year follow-up of the ESTHER study - a German epidemiological study of the elderly population. Trained medical doctors visited n = 3124 participants aged 57 to 84 years in their home. Bio-psycho-social health care needs were assessed using the INTERMED for the Elderly (IM-E) interview. Further information was measured using questionnaires or assessment scales (Barthel index, Patients Health Questionnaire (PHQ) etc.). The segmentation analysis applied a factor mixture model (FMM) that combined both a confirmatory factor analysis and a latent class analysis. Results: In total, n = 3017 persons were included in the study. Results of the latent class analysis indicated that a five-cluster-model best fit the data. The largest cluster (48%) can be described as healthy, one cluster (13.9%) shows minor physical complaints and higher social support, while the third cluster (24.3%) includes persons with only a few physical and psychological difficulties (“minor physical and psychological complaints”). One of the profiles (10.5%) showed high and complex bio-psycho-social health care needs (“complex needs”) while another profile (2.5%) can be labelled as “frail”. Mean values of all psychosomatic variables - including the variable health care costs - gradually increased over the five clusters. Use of mental health care was comparatively low in the more burdened clusters. In the profiles “minor physical and psychological complaints” and “complex needs”, only half of the persons suffering from a mental disorder were treated by a mental health professional; in the frail cluster, only a third of those with a depression or anxiety disorder received mental health care. Conclusions: The segmentation of the older people of this study sample led to five different clusters that vary profoundly regarding their bio-psycho-social needs. Results indicate that elderly persons with complex bio-psycho-social needs do not receive appropriate mental health care.